JEJARING SOSIAL E-WARONG KUBE PKH DALAM UPAYA PENANGANAN KEMISKINAN KASUS PADA E-WARONG CAHAYA DINI KOTA PEKANBARU - Amalia, Ayu Diah (Pusat Penelitian dan Pengembangan Kesejahteraan Sosial, 2018)
Poverty is a multidimensional phenomenon. Poverty can be measured both in terms of economic, sociological, and psychological aspects. This review discusses one of the poverty reduction schemes implemented by the Ministry of Social Affairs through the E-Warong program from a sociological point of view. Particularly the study of the social networks that have been formed in poverty reduction efforts. E-Warong is a place of business and agency that is managed and owned by poor people who receive KUBE, PKH and Rastra programs which are non-cash implementation. This study took the focus on the case of E-Warong Cahaya Dini In Pekanbaru City. How E-Warong Early Light can minimize the poverty seen from the sociological aspect? From the results of E-Warong Cahaya Dini study able to mensharing resources and information, provide support and learning opportunities or build skills on members and others. The handling of poverty in this case is manifested in the accessibility of e-Warong members in capacity building of social capital, skills and income, although not yet significant.